A highly selective and sensitive fluorescent probe for simultaneously distinguishing and sequentially detecting H2S and various thiol species in solution and in live cells. Issue 94 (9th November 2018) - Qiao, Dan; Shen, Tangliang; Zhu, Mengyuan; Liang, Xiao; Zhang, Lu; Yin, Zheng; Wang, Binghe; Shang, Luqing
Abstract : A novel dual-channel mitochondria-targeted fluorescent probe (NCR ) was rationally designed for simultaneously distinguishing and sequentially sensing H2 S, Cys/Hcy, and GSH. Abstract : A novel dual-channel fluorescent probe (NCR ) based on differences in reactivity among H2 S, Cys/Hcy, and GSH was rationally designed for simultaneously distinguishing and sequentially sensing H2 S, Cys/Hcy, and GSH using two emission channels, which also demonstrated thatNCR can be used for targeting mitochondria in mammalian cells.